2017
DOI: 10.1167/17.12.4
|View full text |Cite
|
Sign up to set email alerts
|

Updating of visual orientation in a gravity-based reference frame

Abstract: The brain can use multiple reference frames to code line orientation, including head-, object-, and gravity-centered references. If these frames change orientation, their representations must be updated to keep register with actual line orientation. We tested this internal updating during head rotation in roll, exploiting the rod-and-frame effect: The illusory tilt of a vertical line surrounded by a tilted visual frame. If line orientation is stored relative to gravity, these distortions should also affect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…These results indicate that the eye-centered reference frame, which would be less influenced by the head/body tilt, could also be involved in storing egocentric visuospatial information. Indeed, previous neurophysiological and psychophysical studies have shown that visuospatial information is encoded and stored not in a single reference frame, but in parallel in multiple reference frames ( Tramper & Medendorp, 2015 ; Niehof, Tramper, J. J., Doeller, C. F., & Medendorp, 2017 ; Mullette-Gillman, Cohen, & Groh, 2005 ; Mullette-Gillman, Cohen, & Groh, 2009 ; Caruso, Pages, Sommer, & Groh, 2021 ). Tramper & Medendorp (2015) showed that the bias in a reproduced world-fixed target location (not body-fixed as in the present study) caused by intervening whole-body translation was better explained by a model in which the eye-centered and head/body-centered reference frames were combined than by a model in which each reference frame was used alone.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the eye-centered reference frame, which would be less influenced by the head/body tilt, could also be involved in storing egocentric visuospatial information. Indeed, previous neurophysiological and psychophysical studies have shown that visuospatial information is encoded and stored not in a single reference frame, but in parallel in multiple reference frames ( Tramper & Medendorp, 2015 ; Niehof, Tramper, J. J., Doeller, C. F., & Medendorp, 2017 ; Mullette-Gillman, Cohen, & Groh, 2005 ; Mullette-Gillman, Cohen, & Groh, 2009 ; Caruso, Pages, Sommer, & Groh, 2021 ). Tramper & Medendorp (2015) showed that the bias in a reproduced world-fixed target location (not body-fixed as in the present study) caused by intervening whole-body translation was better explained by a model in which the eye-centered and head/body-centered reference frames were combined than by a model in which each reference frame was used alone.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the eye-centered reference frame, which would be less influenced by the head/body tilt, could also be involved in storing egocentric visuospatial information. Indeed, previous neurophysiological and psychophysical studies have shown that visuospatial information is encoded and stored not in a single reference frame, but in parallel in multiple reference frames (Tramper & Medendorp, 2015;Niehof et al, 2017;Mullette-Gillman et al, 2005Caruso et al, 2021). Tramper & Medendorp (2015) showed that the bias in a reproduced world-fixed target location (not body-fixed as in the present study) caused by intervening whole-body translation was better explained by a model in which the eye-centered and head/body-centered reference frames were combined than by a model in which each reference frame was used alone.…”
Section: Discussionmentioning
confidence: 99%
“…Gravity is known as a critical factor to affect the function of cognition as well as behaviors [1][2][3]. The altered gravity was mainly detected in the peripheral vestibular system, especially otolith, and the corresponding neural information is sent to the central nervous system [4,5].…”
Section: Introductionmentioning
confidence: 99%